Utilization of Cardiac Surveillance Tests in Survivors of Breast Cancer and Lymphoma After Anthracycline-Based Chemotherapy - Ruddy, Kathryn J. (Circ Cardiovasc Qual Outcomes, 2020)
BACKGROUND: The National Comprehensive Cancer Network and American Society of Clinical Oncology recommend consideration of the use of echocardiography 6-12 months after completion of anthracycline-based chemotherapy in at risk populations. Assessment of brain natriuretic peptide (BNP) has also been suggested by the American College of Cardiology/American Heart Association/Heart Failure Society of America for the identification of Stage A (at risk) heart failure (HF) patients. The real-world frequency of the use of these tests in patients after receipt of anthracycline therapy, however, has not been studied previously. METHODS AND RESULTS: In this retrospective study, using administrative claims data from the OptumLabs Data Warehouse, we identified 31,447 breast cancer and lymphoma patients (age ≥ 18 years) who were treated with an anthracycline in the United States between January 1, 2008 and January 31, 2018. Continuous medical and pharmacy coverage was required for at least 6 months prior to the initial anthracycline dose and 12 months after the final dose. Only 36.1% of patients had any type of cardiac surveillance (echocardiography, BNP, or cardiac imaging) in the year following completion of anthracycline therapy (29.7% echocardiography). Surveillance rate increased from 37.5% in 2008 to 42.7% in 2018 (25.6% in 2008 to 40.5% echocardiography in 2018). Lymphoma patients had a lower likelihood of any surveillance compared to breast cancer patients (OR 0.79, 95% CI 0.74-0.85, p<0.001). Patients with pre-existing diagnoses of coronary artery disease and arrhythmia had the highest likelihood of cardiac surveillance (OR 1.54, 95% CI 1.39-1.69 and OR 1.42, 95% CI 1.31-1.53, p<0.001 for both), though no single comorbidity was associated with a >50% rate of surveillance. CONCLUSIONS: The majority of survivors of breast cancer and lymphoma who have received anthracycline-based chemotherapy do not undergo cardiac surveillance after treatment, including those with a history of cardiovascular co-morbidities such as heart failure.